2021
DOI: 10.3389/fphar.2021.600163
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin AT2 Receptor is Anti-inflammatory and Reno-Protective in Lipopolysaccharide Mice Model: Role of IL-10

Abstract: Acute kidney injury (AKI) due to endotoxemic insult is predicted by the infiltration of neutrophils, monocytes and macrophages, and the release of pro-and anti-inflammatory cytokines to the site of injury. Earlier, we have demonstrated the role of angiotensin-II type 2 receptor (AT2R) stimulation in reno-protection in lipopolysaccharide (LPS)-induced inflammation and AKI in C57BL6/NHsd mice. Moreover, AT2R activation has been shown to increase the anti-inflammatory cytokine interleukin-10 (IL-10), its role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
(56 reference statements)
1
8
0
Order By: Relevance
“…These effects, mediated primarily via Mas R stimulation, could also be linked to the proposed interaction between Mas R and AT-2R [18], as AT-2R agonists have been shown to reduce tissue NGAL and KIM-1, biomarkers of kidney injury, following LPS challenge [35]. To the best of our knowledge, no study has currently reported the effects of Ang-(1–7) on kidney perfusion.…”
Section: The Non-canonical Renin Angiotensin System: a Response To Ki...mentioning
confidence: 98%
See 1 more Smart Citation
“…These effects, mediated primarily via Mas R stimulation, could also be linked to the proposed interaction between Mas R and AT-2R [18], as AT-2R agonists have been shown to reduce tissue NGAL and KIM-1, biomarkers of kidney injury, following LPS challenge [35]. To the best of our knowledge, no study has currently reported the effects of Ang-(1–7) on kidney perfusion.…”
Section: The Non-canonical Renin Angiotensin System: a Response To Ki...mentioning
confidence: 98%
“…These findings were further corroborated in a large animal model of septic shock, where high doses of angiotensin-(1-7) treatment limited the development of septic shock and prevented the increase in creatinine and decrease in creatinine clearance, following induction of sepsis via intraperitoneal injection of autologous feces [34 & ]. These effects, mediated primarily via Mas R stimulation, could also be linked to the proposed interaction between Mas R and AT-2R [18], as AT-2R agonists have been shown to reduce tissue NGAL and KIM-1, biomarkers of kidney injury, following LPS challenge [35]. To the best of our knowledge, no study has currently reported the effects of Ang-(1-7) on kidney perfusion.…”
Section: The Non-canonical Renin Angiotensin System: a Response To Ki...mentioning
confidence: 99%
“…Research has shown that AT1R-induced angiogenesis can produce a significant increase in pro-inflammatory cytokines, 17 whereas AT2R was found to be antagonistically reduced angiogenesis. 18 Recent investigation reported that AT1R-mediated positive regulation of NFκB signal activation ultimately induces the overexpression of different cytokines. 19 NFκB is a transcriptional regulator that resides in the cytoplasm when inactive, bound to inhibitor proteins like IκBα or IκBβ.…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin II initiates responses via G protein‐coupled receptors known as AGTR2 (Angiotensin II receptor type‐II), which include AT1R and AT2R. Research has shown that AT1R‐induced angiogenesis can produce a significant increase in pro‐inflammatory cytokines, 17 whereas AT2R was found to be antagonistically reduced angiogenesis 18 . Recent investigation reported that AT1R‐mediated positive regulation of NFκB signal activation ultimately induces the overexpression of different cytokines 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, frontline therapy for patients with CKD includes blockade of the renin-angiotensin system (RAS) using angiotensin II receptor blocker (ARB), or the angiotensin-converting enzyme inhibitor (ACEi), which has been widely reported to control proteinuria and reduce the progression of CKD (Cheung et al, 2021;Chu et al, 2021). Recent discoveries on the activation of angiotensin II type 2 receptors (AT2R) suggest potential therapeutic benefits due to anti-inflammatory and anti-fibrotic properties (Castoldi et al, 2016;Rehman et al, 2012), that may protect from kidney damage and the progression of long-term fibrosis due to AKI (Fatima et al, 2021). Since AT2R therapy was introduced, different types of agonists have been trialled in pre-clinical studies, including the agonists CGP42112 (Whitebread et al, 1989), compound 21 (C21) (Wan et al, 2004) and the antagonist, PD123319 (Dudley et al, 1990).…”
Section: Introductionmentioning
confidence: 99%